ANALISIS ALIH FUNGSI LAHAN PERKEBUNAN KARET DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA DI KECAMATAN MANDIANGIN KABUPATEN SAROLANGUN - Saputri, Jheni Rahmi; Alamsyah, Zulkifli; HD, Ernawati (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to: 1) Describe the description of rubber farming businesses that have converted land and those that have not converted land into oil palm plantations. 2) Analyze the influence of land area, rubber farming income, age of rubber plants, number of family dependents and knowledge on farmers' decisions to convert rubber land into oil palm plantations in Mandiangin District, Sarolangun Regency. The sampling technique used Simple Random Sampling of 88. The analysis method used the Binary Logistic Regression model. From the research results, it was found that (1) The average area of rubber land owned by farmers was 3.4 Ha, with the average area of rubber land converted into oil palm plantations being 2.0 Ha. (2) Land area, rubber farming income, age of rubber plants and the number of farmers' dependents have a significant influence on farmers' decisions regarding land conversion.